Komunikasi Antar Budaya Masyarakat Melayu Dengan Masyarakat Tionghoa Di Sumatera Selatan - Pratama, Muhammad Iqbal (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Communication between Malay and Chinese cultures in South Sumatra reflects the mutual influence and interaction between the two groups.there are various influencing factors, including language, religion, values, traditions and social habits. Language is an important means of intercultural communication. In South Sumatra, Malays generally use Malay as their daily language, while Chinese use Chinese such as Hokkien, Hakka or Mandarin. However, in intercultural communication, there is often an adoption of words or phrases from one language to anotherReligion Also Plays an Important Role in Intercultural Communication. The majority of Malay people in South Sumatra follow Islam, while the majority of Chinese people follow Buddhism, Confucianism or Christianity. These Differences in Religious Beliefs Can Influence Intercultural Communication, But They Also Provide Opportunities for Understanding and Respecting Each Other's Religious Beliefs and Practices. Apart from that, values, traditions and social habits also influence communication between Malay and Chinese cultures in South Sumatra.